Analysis Of Damage And Improvement Of Sledge Cross On Ghb-1340g Lathe Machine - Martoni, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the machining process there are various tools that can be used to help work in the industry. Lathe is one of the machines that can cut metal with the shape, size and quality planned. In this study, the author took the topic of "Analysis and Repair of Latitude Sledge Lathe GHB-1340G". For the process of improving latitude slashes so that the composer can be reused to make improvements in the latitude slashes. After that, the composer conducts an experiment by turning the workpiece sample. The next stage after testing the workpiece samples by making a reduction, holes, and threads obtained a good, smooth, and even turning. The machine does not experience damage or problems anymore and can be used for a good turning process